Corporate management, governance, and ethics best practices - Vallabhaneni, S. Rao.; Association of Professionals in Business Management (Hoboken, N.J. : Wiley, 2008)
"Best practices are the processes, practices, and systems identified in public and private organizations that performed exceptionally well and are widely recognized as improving an organization's performance and efficiency in specific areas. Successfully identifying and applying best practices can improve business processes and increase organizational effectiveness. Based on author S. Rao Vallabhaneni's decades of management experience, Corporate Management, Governance, and Ethics Best Practices provides a one-stop, comprehensive reference guide to the best-of-the-best practices for corporate business practitioners and government employees worldwide."
Ch. 1. Introduction -- Ch. 2. Corporate-Governance Best Practices -- Ch. 3. Corporate-Ethics Best Practices -- Ch. 4. General-Management Best Practices -- Ch. 5. Manufacturing- and Service-Management Best Practices -- Ch. 6. Marketing- and Sales-Management Best Practices -- Ch. 7. Quality-Management Best Practices -- Ch. 8. Process-Management Best Practices -- Ch. 9. Human-Resources Management Best Practices -- Ch. 10. Accounting, Treasury, and Finance-Management Best Practices -- Ch. 11. Information-Technology Management Best Practices -- Ch. 12. International-Business Management Best Practices -- Ch. 13. Project-Management Best Practices.
"Association of Professionals in Business Management."
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Management; Corporate governance; Business ethics; Gestion; Gouvernement d'entreprise.; Morale des affaires; management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; Business ethics; Corporate governance; Management